Environmental, Social, and Governance Disclosure Effects on Firm Value, Profitability, and Capital Structure in Indonesia - Wardhana, Ananda Ayyub; Hersugondo (LifeSciFi, 2025)
This investigation explores the intricate interplay between Environmental, Social, and Governance (ESG) disclosures and their impact on corporate valuation and profitability, with capital structure serving as a pivotal mediating factor. Despite growing stakeholder interest in ESG practices, research findings remain inconsistent, particularly in emerging markets. Drawing upon rigorous quantitative techniques and the application of PLS-SEM analysis, our study meticulously examined a sample of 42 publicly traded companies on the Indonesia Stock Exchange spanning the years 2017 to 2023. The findings illuminate a nuanced landscape: environmental disclosure exerts a positive influence on profitability, yet its impact on firm value remains statistically insignificant. Conversely, social disclosure emerges as a significant driver of firm value, although it does not markedly enhance profitability. Intriguingly, disclosures related to governance reveal a paradoxical negative association with profitability, challenging conventional assumptions about transparency and firm performance. Capital structure plays a significant mediating role, with environmental disclosure showing positive indirect effects on both performance metrics, while social disclosure exhibits negative indirect effects. These findings contribute to understanding ESG implementation dynamics in emerging markets, highlighting how each ESG component influences corporate performance through distinct pathways. The study offers practical insights for companies integrating sustainability practices, suggesting that strategic alignment between ESG initiatives and financial management is crucial for optimizing performance outcomes in Indonesia's evolving business landscape.